V italijanskih testeninah na papirju in spletu - Stritar Kučuk, Mojca (Jezik in slovstvo, 2022)
The article analyses a case-oriented grammatical task undertaken by South Slavic speakers of Slovenian as L2. Students learning Slovenian in the Year Plus module are compared in two groups: one solved the test on paper, while the other learned Slovenian partly online and also took the test online. Cases proved difficult for all of the students, with the most challenging being the locative in plural and the non-prepositional use of the dative. The group that took the exam online was more successful, supposedly due to less teacher control during the exam and thus easier access to various language tools. However, the speakers in this group made more spelling and lexical errors. The Macedonian students were more successful than the Bosnian, Croatian, Montenegrin and Serbian students, particularly those from the group that took the test online.
Keywords: distance learning; grammatical competence; jezikovno testiranje; language testing; noun; samostalnik; Slovenian; Slovenian as a second language; slovenščina; slovenščina kot drugi jezik; slovnična zmožnost; učenje na daljavo